Uneven distribution of enamel, dentine and cementum in cheek teeth of domestic horses (Equus caballus) : A micro computed tomography study - Englisch, Lauritz Martin; Kostrzewa, Kathrin; Kopke, Susan; Failing, Klaus; Staszyk, Carsten; Justus Liebig University Giessen (My University, 2017)
Background: Hypsodont equine cheek teeth possess large dental crowns, resting partly in the bony alveolus. Over a horse s life cheek teeth erupt continuously to compensate for occlusal wear of 3 4 mm per year. Parts of the crown initially resting in the bony alveolus become progressively exposed at the occlusal surface with time. Hitherto, it is unclear whether the typical structure of the equine occlusal surface, composed of a complex arrangement of enamel, dentin and cementum, remains constant or undergoes structural changes with age. Therefore, we tested the hypothesis that the occlusal surface composition does not remain constant by a quantitative analysis of the dental substances at multiple levels along the dental crown of equine cheek teeth. Methods: Micro-computed tomography scans of 20 upper cheek teeth and 16 lower cheek teeth from 19 domestic horses were morphologically analysed using imaging and measurement software. Area for individual dental substances was measured at different levels from the apex to the occlusal surface. The data was statistically analysed to detect changes in the area of individual substance along the dental crown. The area of peripheral cementum was measured separately for levels inside and outside the bony alveolus. Results: In both, upper and lower cheek teeth, enamel area decreased in an apical direction, while dentine area increased. Peripheral Cementum increased dramatically in the occlusal/coronal extra-alveolar position. Conclusion: With increasing age the occlusal surface content of dentine increases while the content of enamel decreases. These changes are considered relevant for the detailed explanation of forage disruption in horses as well as for the recommendation of concepts in equine dentistry.
Keywords: ddc:630